A methodology for performance evaluation and system loss analysis of photovoltaic power plants: case studies in Vietnam - Truong, Le Phuong; Tri, Bui Van; Long, Le Phuong (Institute of Advanced Engineering and Science, 2024)
This study presents a methodology for performance evaluation and loss analysis of two photovoltaic (PV) power plants in Vietnam with different geographical locations and climatic conditions. An experimental methodology is utilized to analyze the system losses. Data was collected from the BIM2 (250 MWp) and Buon Ma Thuot (35 MWp) plants. The results show that system losses do not exceed 1.3%, with performance rates ranging from 73-79% for BIM2 and 74-88% for Buon Ma Thuot. Correlation analysis between module operating temperature, solar irradiance, and energy yield reveals an inverse relationship between the temperature-irradiance ratio and energy yield. A considerable decline in power plant efficiency is observed when this ratio exceeds 8. Additionally, vital monitored indices for PV plant operation are investigated, including energy supplied to the grid, PV array temperature, ambient temperature, and loss metrics.